2022
DOI: 10.2147/ijgm.s354882
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of a Ferroptosis-Related Signature for Predicting Prognosis and Immune Microenvironment in Papillary Renal Cell Carcinoma

Abstract: Objective We aimed to explore the prognostic patterns of ferroptosis-related genes in papillary renal cell carcinoma (PRCC) and investigate the relationship between ferroptosis-related genes and PRCC tumor immune microenvironment. Methods We obtained the mRNA expression and corresponding clinical data of PRCC from the public tumor cancer genome atlas database (TCGA). The PRCC patients were randomly divided into two cohort, training cohort and verification cohort, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A close link exists between MIOX and cancer ferroptosis. For example, studies revealed that MIOX is involved in ferroptosis-related gene models in papillary thyroid carcinoma, bladder cancer and papillary renal cell carcinoma [ 12 , 13 , 56 ]. Zhang et al reported that MIOX could suppress the progression of hepatocellular carcinoma by increasing ROS production, reducing the levels of NADPH and GSH and accelerating ferroptosis induced by erastin and RSL3 [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A close link exists between MIOX and cancer ferroptosis. For example, studies revealed that MIOX is involved in ferroptosis-related gene models in papillary thyroid carcinoma, bladder cancer and papillary renal cell carcinoma [ 12 , 13 , 56 ]. Zhang et al reported that MIOX could suppress the progression of hepatocellular carcinoma by increasing ROS production, reducing the levels of NADPH and GSH and accelerating ferroptosis induced by erastin and RSL3 [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…CDKN1A has been shown to be a member of ferroptosis-associated signature genes to predict graft loss after renal allograft transplantation ( Fan et al, 2021 ). Moreover, the prognosis of KIRP patients can also be accurately predicted by the risk model constructed by using CDKN1A as a ferroptosis-related gene signature ( Da et al, 2022 ). A study in a mouse model identified CDKN1A as a target of phagocytosis-mediated immunotherapy of acute leukemia cells, CDKN1A promotes phagocytosis of leukemia cells and subsequently promotes pro-inflammatory reprogramming of phagocytic macrophages via interferon Gamma extends to surrounding macrophages, presenting the therapeutic opportunity for cancer therapy ( Allouch et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“… 111 On the other hand, it can inhibit ferroptosis by inhibiting dipeptidyl peptidase 4 (DPP4) activity or by promoting the expression of cell cyclin-dependent kinase inhibitor 1A (CDKN1A/p21). 112 …”
Section: Regulation Of Intracellular Biochemical Processes On Ferropt...mentioning
confidence: 99%